Pacific peoples' wellbeing: Background paper to Te Tai Waiora: Wellbeing in Aotearoa New Zealand 2022 - Su'a Thomsen; Hamed Shafiee; Amy Russel (New Zealand Government, The Treasury, 2023)
This paper is part of a series of detailed background papers designed to support Te Tai Waiora, the Treasury's first Wellbeing Report, which was published in November 2022. New Zealand is home to the world's largest Pacific population. About one in 12 New Zealanders identifies as having a Pacific ethnicity or ethnicities, and the Pacific population is much younger and faster growing than the general population. As the Pacific population continues to grow, so too does their influence and importance to wellbeing in New Zealand. Pacific New Zealanders have a significant potential to materially contribute to the country's social and economic prosperity. Equally, risks to the wellbeing of Pacific New Zealanders are increasingly risks to the wellbeing of all New Zealanders.
Keywords: 330; Sozialer Indikator; Ozeanier; Neuseeland